Gastroesophageal reflux disease with proton pump inhibitor use is associated with an increased risk of osteoporosis: a nationwide population-based analysis. Issue 6 (June 2016) - Chen, C.-H.; Lin, C.-L.; Kao, C.-H.
Abstract Summary Gastroesophageal reflux disease (GERD) with proton pump inhibitor (PPI) use is associated with an increased risk of osteoporosis. The risk of hip fracture is not increased in GERD patients with PPI use. Introduction The relationship between GERD with PPI treatment and the risk of osteoporosis is unclear. We aimed to determine the risk of developing osteoporosis in patients diagnosed with GERD. Methods Patients diagnosed with GERD and received PPI treatment between 2000 and 2010 were identified from the Longitudinal Health Insurance Database as the study cohort (n  = 10, 620), which was frequency matched with the comparison cohort (n  = 20, 738) sampled from the general population according to age, sex, index year, and comorbidities. Both cohorts were followed until the end of 2011. The risk of osteoporosis was evaluated in both groups by using Cox proportional hazards regression models. Results The GERD patients with PPI treatment had a greater incidence (31.4 vs 20.7 per 1000 person-year; crude hazard ratio [cHR] 1.51; 95 % confidence interval [CI] 1.40–1.63) and a higher risk (adjusted HR [aHR] 1.50; 95 % CI 1.39–1.62) of osteoporosis than that of the comparison cohort. However, the overall incidence of hip fracture was not different between the GERD with PPI use and the control cohorts (aHR 0.79; 95 % CI 0.53–1.18). Conclusion GERD with PPI use is associated with an increased risk of osteoporosis. The findings of our study do not support an increased risk of hip fracture in GERD patients treated with a PPI.